Dementia care from behind the mask? Maintaining well‐being during COVID‐19 pandemic restrictions: Observations from Dementia Care Mapping on NHS mental health hospital wards in Wales. Issue 6 (28th April 2021) - Page, Sean; Davies‐Abbott, Ian; Jones, Adrian
Accessible summary: What is known on the subject?: Coronavirus disease 2019 (COVID‐19) is a new infectious disease that has spread across the world and infected a large number of people many of whom have died. People with moderate to severe dementia are at very high risk of becoming infected as the disease mainly impacts on older people with other health problems and once infected the person with dementia is more likely to become seriously ill than other people. To prevent infection, people are required to wear masks and isolate from contact with others. It is believed that these measures can reduce the quality of life and general well‐being of people with moderate to severe dementia in hospital or social care. This belief has not yet been demonstrated by research. What does this paper add to the existing knowledge?: We show that people with moderate to severe dementia receiving care on mental health hospital wards and subject to strict infection prevention measures can still achieve high levels of well‐being. We show that mental health nurses alter the focus of their care to deliberately overcome the challenges and particularly the restrictions on visiting by families. What are the implications for practice?: We believe that the changes in practice we observed can occur in other healthcare and social care settings and that whilst restrictions remain in place care staff can protect and possibly enhance well‐being for people with moderate to severe dementia. Abstract: Introduction: The effect of coronavirus (COVID‐19) on people living with dementia is potentially severe in its clinical impacts. More widely, for this vulnerable group, the social restrictions to limit the spread of infection may be emotionally and psychologically damaging. Aim: To explore the impact of restrictions on well‐being for people with moderate to severe dementia in acute mental health hospital care. Method: "Dementia Care Mapping" was the observational tool used to determine well‐ or ill‐being. Observations were undertaken in two mental health hospital wards during a time of restrictions and the use of personal protective equipment. Results: We report levels of well‐being that are higher than might be expected alongside a change in the focus of psychological care delivered through mental health nursing interventions aimed at enhancing well‐being. Discussion—We postulate that mental health nurses faced with an unprecedented challenge respond by changing practice to mitigate for infection prevention measures and to compensate for family absence. Implications for practice: We suggest that the desirable enhancing actions by nursing staff which raise well‐being in these hospital settings are readily transferable to other settings that are aiming to maintain well‐being but also practising under COVID‐19 restrictions.